Chagas Disease Expands Its Epidemiological Frontiers From Rural to Urban Areas - Alarcón de Noya, Belkisyole; Díaz-Bello, Zoraida; Ruiz-Guevara, Raiza; Noya, Oscar (Frontiers in Tropical Diseases, 2022)
The infection by the hemoflagellate parasite Trypanosoma cruzi originates from America where the wild life cycle remains alternating between mammals and hematophagous triatomines. Transmission through contamination of the bite site by vector feces containing highly infectious forms of parasite or direct ingestion of T. cruzi-infected triatomines appear to be the dominant transmission mechanisms. Man joins the transmission when he enters this wild environment or takes the palms leaves with vectors to build houses. This is how rural Chagas disease develops associated with populations with low economic resources, the presence of the vector, episodes of infection and reinfection from childhood and the consequent evolution toward chronic cases in adults, when there is little therapeutic benefit to infected people. The progressive migration of people from rural to urban areas, the adaptation of vectors to the peripheries of cities due to displacement caused by deforestation or urbanization that has favored the presence of enzootic cycles with Panstrongylus geniculatus as the most widely distributed species and mammals (synanthropic and domestic) allow vector transmission by ingestion of food contaminated with excrements containing infectious trypomastigotes as the dominant transmission mechanism in the urban environment. Human-to-human transmission through vertical mother-child infection, transfusions, organ transplants and the possibility of sexual transmission, transform the epidemiology and the clinical evolution of Chagas disease in the urban environment. Vectors of American Trypanosomiasis are not longer restricted to the endemic area but its presence has been demonstrated in non-endemic areas of the United States, Asia and other latitudes. The worldwide plague of bedbugs (Cimex lectularius) threatens the possibility of expansion of transmission since they are vectors susceptible to infection, transmission to mammals, trans-stadial penetration and not being affected by T. cruzi infection at least experimentally. These factors, added to the presence of an unknown number of Latin American carriers of the parasite exported to the world, may eventually become a global public health problem if control measures based on vaccine research, new anti-parasitic drugs, active search for human cases, treatment of infected children and epidemiological surveillance of vectors and food preparation as well.